Specification of variables predictive of victories in the sport of boxing : II. Further characterization of previous success - Warnick, J. E.; Warnick, K. (Perceptual and Motor Skills, 2009)
Previous success, i.e., performance in the preceding bout and total number of wins and losses, was predictive of victory. Clarification of this effect was sought in examining whether the prior performance against a particular opponent or in a common location would be predictive of a victory in a bout against that opponent or in that locale. The career records of 739 male professional boxers who participated in contests held in the USA in November 2007 were collected from the BoxRec online database. Chi-squared tests and logistic regression analyses indicated that performance in the preceding bout, prior performance against the same opponent, and prior performance in a particular location were predictive of the outcome in a current bout.